2x-(4x-9)=6-x

Simple and best practice solution for 2x-(4x-9)=6-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(4x-9)=6-x equation:


Simplifying
2x + -1(4x + -9) = 6 + -1x

Reorder the terms:
2x + -1(-9 + 4x) = 6 + -1x
2x + (-9 * -1 + 4x * -1) = 6 + -1x
2x + (9 + -4x) = 6 + -1x

Reorder the terms:
9 + 2x + -4x = 6 + -1x

Combine like terms: 2x + -4x = -2x
9 + -2x = 6 + -1x

Solving
9 + -2x = 6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
9 + -2x + x = 6 + -1x + x

Combine like terms: -2x + x = -1x
9 + -1x = 6 + -1x + x

Combine like terms: -1x + x = 0
9 + -1x = 6 + 0
9 + -1x = 6

Add '-9' to each side of the equation.
9 + -9 + -1x = 6 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = 6 + -9
-1x = 6 + -9

Combine like terms: 6 + -9 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x-35=27 | | 5x+3(4-6x)=11 | | 5/11=u/10 | | 8y-3=-4y+6 | | 2x-35=37 | | 2x^2+13x+8=2 | | f(a-4)=5x+2 | | 4/5k-6 | | 4/5k--6 | | 100=6x+4 | | 3x+-3=-9 | | 7.3=8.5-0.6x | | 15=8x+3-6 | | -6y=1/4 | | (2x-4)*x=100 | | 3x/(x^2-x-20) | | 3x/x^2-x-20 | | 1nx=6 | | 2x-4*x=100 | | C=8pieg | | y=-3z-4 | | 1/(3y)=1/24 | | 3(7+w)=2(6+w) | | -25=4x-4 | | 7.4x-3.8=18.4 | | 6(x+4)+2=8x-2(x-5) | | 3x+4x-4=24 | | -2x+35=2x+15 | | Cos(x)-Cos^3(x)= | | 36x-9/2x^2 | | 3x(x+2)=7 | | 3x(x-2)=7 |

Equations solver categories